SYSTEM PERFORMANCES OF SC RECEPTION IN ASYMMETRIC MULTIPATH FADING ENVIRONMENTS - Đošić, Danijel; Stefanović, Časlav; Milić, Dejan; Stefanović, Mihajlo (Bulletin of Natural Sciences Research, 2019)
The paper takes into consideration dual-branch selection combining (SC) diversity reception technique in the presence of dissimilar fading at their branches. We efficiently obtained first and second order closed form statistics at the output of the considered model such as probability density function (PDF), cumulative distribution function (CDF) and average level crossing rate (aLCR). Moreover, obtained results are numerically presented for various sets of system model parameters and mainly confirmed by computer based MATLAB simulations.
Keywords: Selection combining (SC); Nakagami-m random variable; α-μ random variable; PDF; CDF; aLCR